Pengaruh Edukasi Tentang Akupresur dan Pijat Oksitosin Terhadap Pengetahuan Mahasiswa Poltekkes Jambi Jurusan Kebidanan - Pauline Kusmaryati; Netti Herawati; Ajeng Galuh Wuryandari (NHM PRESS, 2022)
One type of traditional health services that can be integrated at the Puskesmas is acupressure. Acupressure to increase the amount of breast milk can be done by massaging at the intersection of the perpendicular lines from the corner of the little finger nail. Oxytocin massage is one solution to overcome the uneven production of breast milk. The purpose of this study was to develop educational media for acupressure and oxytocin massage for Jambi Midwifery Department students at the Jambi Polytechnic. The type of research was quasi-experimental using a pretest posttest design without control design which involved 36 students from the Jambi Polytechnic of Health in the Midwifery Department who had been held in May-November 2022, and were selected using a purposive sampling technique. This research was conducted from May to November 2022. Analysis of research data used a non-parametric test, namely the Wilxocon test. The results showed that there were differences in the level of knowledge before and after the intervention where before the intervention the minimum knowledge score was 5 and then increased to 9 after the intervention. Statistically, it shows that there is a significant difference in students' knowledge scores before and after the intervention (p-value <0.05). The conclusion of the study is that education about acupressure and oxytocin massage is effective in increasing student knowledge.